The Influence of Curriculum Assistance and School Working Climate of High School Teacher Piloting Curriculum 2013 in Palu City - Faisah, Nurul; Ramadhan, Achmad; Tangge, Lilies N. (Jurnal Riset Pendidikan MIPA, 2017)
The purpose of this research is to analyze the influence of 1) The assistance of curriculum partially on the teachers' performance. 2) The school working climate partially influenced teachers' performance. 3) The assistance of curriculum and working climate simultaneously influenced the teacher. The method that I used was descriptive quantitative. The population of this research is senior high school teachers piloting curriculum 2013 in Palu which consists of 50 people in 21 % total sampling. The technique of data analysis is multiple regression analysis. The results showed that: 1) The Assistance of curriculum has a negative effect and significantly to the teacher performance, 2) school working climate has a positive influence and significance to the teacher performance. 3) The assistance of curriculum simultaneously and school working climate has a significant influence on teachers' performance. The contribution of curriculum assistance influence and school working climate on teachers performance was 24.7 %, while 75.3 % was influenced by the other factors.